SAP Signavio: Revolutionizing Business Process Management in the Cloud - Kiran Kumar Lekkala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
SAP Signavio offers a transformative cloud-based process management and workflow automation platform that enables organizations to streamline operations, reduce costs, and improve efficiency. This article explores how SAP Signavio disrupts traditional business process management paradigms through its cloud-native approach, democratizing process capabilities across organizations regardless of size. The platform's core capabilities include BPMN 2.0 process modeling, advanced analytics, end-to-end automation, and collaborative governance features. Its native integration with the broader SAP ecosystem creates a cohesive environment for comprehensive process management. The article examines SAP Signavio's significant business impact across industries, including manufacturing, financial services, healthcare, and retail, highlighting improvements in operational excellence, regulatory compliance, customer experience, and digital transformation enablement. Implementation considerations, including process maturity assessment, stakeholder engagement, integration planning, and change management, are discussed as critical success factors for organizations seeking to maximize their return on investment.
Keywords: Process Management; Business Process Automation; Digital Transformation; SAP Integration; Process Excellence; Cloud-Based Workflow